High-G inertial MEMS accelerometers - Vinayak Narasimhan (2015)
This thesis reports work done towards two novel high-G MEMS accelerometer projects, the first being a monolithically fabricated high-G triaxial MEMS accelerometer structure. This device consists of three independent and isolated sensing elements dedicated to measuring acceleration inputs along each of the three primary sensing axes. The sensor design is made as symmetrical and compact as possible to simplify the fabrication and reduce the overall bulk size of the die. The thesis documents work done towards the conceptualization, simulation and fabrication of this complex MEMS structure array. The second project covers an exciting and rapidly evolving area of MEMS design. It is the CMOS-MEMS integration. This particular approach provides a host of advantages when compared with existing hybrid set-ups particularly towards high-g sensing as discussed in later sections. The device employing capacitive sensing is designed and fabricated based on IMEC's much sought after SiGe MEMS (Silicon-Germanium based) process where the MEMS is processed after and on top of the CMOS readout circuitry.